Preparation and Role Performance of Heads of Secondary Schools in the Ashanti Region of Ghana: Lessons to Draw - Boadu, Kankam (Advances in Social Sciences Research Journal, 2021)
This study examined how Senior Secondary School heads were prepared for their roles and if their preparation have bearings on their role performance. The research design adopted for this study was descriptive survey. In all, a sample of 51 heads of Senior Secondary School in the Ashanti Region of Ghana were purposively selected and assessed. A 21-item questionnaire consisting of both open and close ended items was used. The data was analysed using percentages and chi-square. Analysis of the data showed that majority of the heads have not had any advanced preparation for their roles and that they faced challenges in their day to day performance of their roles. The recommendations made among other things are that there should be succession plan for prospective heads of institutions so that when they eventually assume heads positions, they are not found wanting. More so, there should be manuals for heads of institutions to guide the newly appointed. Lastly, it is recommended that regular seminars and in-service training be organised for heads of institutions so that they share ideas and learn from best practices.